Intelligent Systems and Machine Learning First EAI International Conference, ICISML 2022, Hyderabad, India, December 16-17, 2022, Proceedings, Part II - Nandan Mohanty, Sachi; Garcia Diaz, Vicente; Satish Kumar, G. A. E. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This two-volume set constitutes the refereed proceedings of the First EAI International Conference on Intelligent Systems and Machine Learning, ICISML 2022, held in Hyderabad, India, in December 16-17,2022. The 75 full papers presented were carefully reviewed and selected from 209 submissions. The conference focuses on Intelligent Systems and Machine Learning Applications in Health care; Digital Forensic & Network Security; Intelligent Communication Wireless Networks; Internet of Things (IoT) Applications; Social Informatics; and Emerging Applications.
Intelligent Systems and Machine Learning Applications in Health care -- Improving Multi-class Brain Tumor Detection using Vision Transformer as Feature Extractor -- Measles rash disease classification based on various CNN classifiers -- BRAIN IMAGING TOOL IN PATIENTS WITH TRANS ISCHEMIC ATTACK: A COMPARITIVE RESEARCH STUDY ANALYSIS OF COMPUTED TOMO -- EEG-based Stress Detection Using K-Means Clustering Method -- Detection of Psychological Stability Status Using Machine Learning Algorithms -- GLCM Based Feature Extraction and Medical X-ray Image Classification Using Machine Learning Techniques -- Multi filter wrapper enhanced machine learning model for cancer diagnosis -- An Interactive Web Solution for Electronic Health Records Segmentation and Prediction -- A Convolutional Neural Network based Prediction Model for Classification of Skin Cancer Images -- Multimodal Biomedical Image Fusion Techniques in Transform and spatial Domain: An Inclusive Survey -- Early Prediction of Coronary Heart Disease Using the Boruta Metho -- Design and Implementation of Obesity Healthcare System (OHS) using Flutter Platform -- A Survey on Covid-19 Knowledge Graphs and their Data Sources -- Identify Melanoma using CNN -- Digital Forensic & Network Security -- Machine Learning based Malware Analysis in Digital Forensic with IoT Devices -- Malicious Codes Detection : Deep Learning Techniques -- Securing Outsourced Personal Health Records On Cloud Using Encryption Techniques -- Design and Evaluation Decentralized Transactional Network Based Blockchain Technology using Omnet++ -- Movie Synchronization System using Web Socket based Protocol -- A Study on Android Malware Detection using Machine Learning Algorithms -- Intelligent Communication Wireless Networks -- A Survey on Deep Recurrent Q networks -- Predicting Credit Card Defaults with Machine Learning Algorithm using Customer Database -- Enhancement of Signal to Noise Ratio for QAM signal in Noisy channel -- GSM ENABLED PATIENT MONITORING SYSTEM USING ARDUINO APPLICATION FOR CARDIAC SUPPORT -- Reso-Net: Generic Image Resolution Enhancement Using Convolutional Autoencoders -- Smart Traffic System with Green Time optimization using Fuzzy logic -- Early Diagnosis of Rheumatoid Arthritis of the Wrist Using Power Doppler Ultrasound: A Review -- An intrusion detection System and Attack Intension used in Network forensic exploration -- Comparison of Advanced Encryption Standard Variants Targeted at FPGA Architectures -- Characteristics and Analysis of ElectroGastroGram Signal -- A COMPARATIVE STUDY OF POWER OPTIMIZATION USING LEAKAGE REDUCTION TECHNIQUES -- Design and Implementation of 4-bit High Speed Array Multiplier for Image CodingDesign and Implementation of 4-bit High Speed Array Multiplier for Image Coding -- Internet of Things (IoT) Applications -- Smart Traffic Police Helmet: Using Image Processing and IoT -- Interconnected Hospitals using IOT -- Automatic oxygen ventilation and monitoring system using IoT -- Social Informatics -- Social Media Sentiment Analysis Using Deep Learning Approach -- Movie Recommendation Using Content-Based and Collaborative Filtering Approach -- Movie Recommendation Using Content-Based and Collaborative Filtering Approach -- Movie Recommendation System using Composite Ranking -- SOCIAL DISTANCING AND FACE MASK DETECTION USING OPEN CV -- Predicting the Likeliest Customers; Minimizing Losses on Product Trials using Business Analytics -- Television price prediction based on features with Machine Learning -- Emerging Applications -- A Model for Engineering, Procurement, and Construction (EPC) Organizations Using Vendor Performance Rating System -- F2PMSMD: Design of a Fusion model to identify Fake Profiles from Multimodal Social Media Datasets -- A Novel Model To Predict The Whack Of pandemics On The International Rankings Of Academia -- Mining Ancient Medicine Texts Towards an Ontology of Remedies - A Semi-automatic Approach -- A Blockchain Enabled Medical Tourism Ecosystem -- Measuring the impact of oil revenues on government debt in selected countries by using ARDL Model -- DIAGNOSIS OF PLANT DISEASES BY IMAGE PROCESSING MODEL FOR SUSTAINABLE SOLUTIONS -- Face Mask Detection: An Application of Artificial Intelligence -- A critical review of Faults in cloud computing: Types, Detection, and Mitigation schemes -- VIDEO CONTENT ANALYSIS USING DEEP LEARNING METHODS -- Prediction of Cochlear Disorders using face tilt estimation and Audiology dataset -- Quantum Data Management and Quantum Machine Learning for Data Management: State-of-the-Art and Open Challenges -- Multivariate Analysis and Comparison of Machine Learning Algorithms: A case study of Cereals of America -- Competitive Programming Vestige using Machine Learning -- Machine Learning Techniques for Aspect Analysis of Employee Attrition -- AI-Enabled Automation Solution for Utilization Management in Healthcare Insurance -- Real-Time Identification of Medical Equipment using Deep CNN And Computer Vision -- Design of a intelligent crutch tool for elders -- An approach to new technical solutions in resource allocation based on artificial intelligence -- Gesture Controlled Power Window Using Deep Learning -- Novel Deep Learning techniques to design the model and Predict Facial Expression, gender, and age recognition -- A Comprehensive Review on Various Data Science Technologies used for Enhancing the Quality of Education Systems -- AI/ML Based Sensitive Data Discovery and Classification of Unstructured Data Sources -- AI/ML Based Sensitive Data Discovery and Classification of Unstructured Data Sources -- Machine Learning Based Spectrum sensing for Secure data Transmission using Cuckoo search optimization.
Keywords: Artificial intelligence; Artificial Intelligence